Criticism of the Social Doctrine of the Catholic Church in the Communist Lithuanian Press (1917-1940) - Mikuckas, Pranas (Problemos, 1974)
The paper analyses the way the communist Lithuanian press, fighting under the hard underground conditions in 1917-1940 against political clericalism in Lithuania, criticized the social doctrine of the Catholic Church, disclosing its antidemocratic essence and pseudo-scientific character. Both the character and content of the criticism of the social doctrine of the Catholic Church were determined in the communist Lithuanian press by the Marxist-Leninist principle of the struggle against religion and reactionary ideology, and by the actual circumstances of the revolutionary struggle. To the distorted, mystified understanding of capitalist society and its social problems propounded by the social doctrine of Catholicism the communist press in Lithuania opposed the class proletarian understanding of the antagonistic society and showed what purpose all those “theories” of Catholic sociology served. This exactly is its contribution to the Marxist-Leninist criticism of the Catholic sociology in Lithuania.